Image Processing And Analyzing Using Wavelet By Applying Java - Xiao, Kai (2003)
Project overview and objective Within the process of transporting medical images to doctors for viewing, some medical images have very high resolution, and some images is very big in size which would be difficult or impossible to display on computer screen or PDA. To make a better vision for doctors, it’s desirable to develop a multi-resolution display method which doctors may view images by second option of viewing the compressed image in accompany with browsing and moving the image of original size in the computer screen or PDA. The problem rise while some compressed image may not be able to recognize for some special usage like medical and scientific research, and getting a sound resolution for viewer to understand immediately what some important details are is needed before compressed file transferred. Within my dissertation, I use Wavelet as the approach of developing the multi-resolution display and give out a fully developed software program including Haar and Debauchies wavelet analysis and synthesis, saving all related data and area image files, generated relevant graph chart on color information histogram in supporting it. After getting the generated color data text file, I use Microsoft Excel to do some data analysis to get the final result on knowing what are the subjective criteria for a recognizable or readable image comparing with the original image. In this report, I explain the algorithm of Wavelet whose Mother function is Haar and Debauchies 53 and 97, and I also explain the implementation on this algorithm using Java by using some of code as examples. Finally, I put my own subjective algorithm as criteria for the readable image compress rate.